Geopolitical analysis of the relocation of Indonesia’s capital city to the archipelago’s capital city, East Kalimantan - Agus Haryanto,; Arief Bakhtiar Darmawan, (Penerbit UKM, 2024)
This research aims to analyse the geopolitical arguments for the policy of relocating Indonesia’s capital city to the Ibu Kota Nusantara (IKN) located in East Kalimantan. IKN is located in the central region of Indonesia, allowing development policies to reduce the burden on Jakarta and Java Island and equalising development in central and eastern Indonesia. Geopolitical analysis is needed to thoroughly observe the reasons and policies the Indonesian government must carry out to be relevant to the contemporary geopolitical situation. This research uses a qualitative research method using literature study as a secondary source. The results show that Indonesia needs to make five changes to utilise the potential of IKN and its strategic location. In terms of changes in priority setting, Indonesia needs to emphasise equitable development. Second, regarding security and defence policy, Indonesia must build maritime resilience for shipping and trade. Third, regarding economic and trade policies, Indonesia must direct economic and trade connectivity related to natural resource exports. Fourth, regarding environmental and maritime policies, Indonesia needs to ensure that development and environmental conditions can go hand in hand to attract foreign investors. Fifth, Indonesia’s regional and global diplomacy priorities lead to an Indo-Pacific stability and security strategy to make the region a global growth epicentrum.